Identification of Novel and Differentially Expressed MicroRNAs of Dairy Goat Mammary Gland Tissues Using Solexa Sequencing and Bioinformatics - Ji, Zhibin; Wang, Guizhi; Xie, Zhijing; Wang, Jianmin; Zhang, Chunlan; Dong, Fei; Chen, Cunxian (PLOS ONE, 2012)
MicroRNAs are small, noncoding RNA molecules that regulate gene expression at the post-transcriptional level and play an important role in various biological processes. Although most microRNAs expression profiles studies have been performed in humans or rodents, relatively limited knowledge also exists in other mammalian species. The identification of the full repertoire of microRNAs expressed in the lactating mammary gland of Capra hircus would significantly increase our understanding of the physiology of lactating mammary glands. In this study, two libraries were constructed using the lactating mammary gland tissues of Laoshan dairy goats (Capra hircus) during peak and late lactation. Solexa high-throughput sequencing technique and bioinformatics were used to determine the abundance and differential expression of the microRNAs between peak and late lactation. As a result, 19,044,002 and 7,385,833 clean reads were obtained, respectively, and 1,113 conserved known microRNAs and 31 potential novel microRNA candidates were identified. A total of 697 conserved microRNAs were significantly differentially expressed with a P-value<0.01, 272 microRNAs were up-regulated and 425 microRNAs were down-regulated during peak lactation. The results were validated using real-time quantitative RT-PCR. 762,557 annotated mRNA transcripts were predicted as putative target gene candidates. The GO annotation and KEGG pathway analysis suggested that differentially expressed microRNAs were involved in mammary gland physiology, including signal transduction, and cell-cell and cell-extracellular communications. This study provided the first global of the microRNA in Capra hircus and expanded the repertoire of microRNAs. Our results have great significance and value for the elucidation of complex regulatory networks between microRNAs and mRNAs and for the study of mammary gland physiology and lactation.